Ribosomal protein S27-like is a physiological regulator of p53 that suppresses genomic instability and tumorigenesis - Xiufang Xiong; Yongchao Zhao; Fei Tang; Dongping Wei; Daffyd Thomas; Xiang Wang; Yang Liu; Pan Zheng; Yi Sun (eLife, 2014)
Cell-based studies showed that several Mdm2-binding ribosomal proteins, upon overexpression, stabilize and activate p53. In contrast, here we show in a mouse knockout study that Mdm2-binding ribosomal protein S27-like (Rps27l), upon disruption, activates p53. Germline inactivation of Rps27l triggers ribosomal stress to stabilize Mdm2, which degrades Mdm4 to reduce Mdm2-Mdm4 E3 ligase towards p53, leading to p53-dependent apoptotic depletion of hematopoietic stem cells and postnatal death, which is rescued by Trp53 deletion. Paradoxically, while increased p53 is expected to inhibit tumorigenesis, Rps27l−/−;Trp53+/− mice develop lymphomas at higher incidence with p53 loss-of-heterozygosity and severe genome aneuploidy, suggesting that Rps27l disruption impose a selection pressure against p53. Thus, Rps27l has dual functions in p53 regulation: under Trp53+/+ background, Rps27l disruption triggers ribosomal stress to induce p53 and apoptosis, whereas under Trp53+/− background, Rps27l disruption triggers genomic instability and Trp53 deletion to promote tumorigenesis. Our study provides a new paradigm of p53 regulation.